Placental expression of the insulin receptor binding protein GRB10: Relation to human fetoplacental growth and fetal gender. Issue 11 (November 2015) - Mukhopadhyay, A.; Ravikumar, G.; Dwarkanath, P.; Meraaj, H.; Thomas, A.; Crasta, J.; Thomas, T.; Kurpad, A.V.; Sridhar, T.S.
Abstract: Introduction: Imprinted genes play an important role in mammalian fetoplacental growth and development. We have evaluated whether the placental expression of two imprinted genes, growth factor receptor-binding protein 10 ( GRB10 ) and pleckstrin homology-like domain, family A, member 2 ( PHLDA2 ) correlate with human fetoplacental growth parameters. Methods: Placentae (n = 77) were collected from small- (SGA) and appropriate- (AGA) for gestational age full-term singleton pregnancies (n = 36 SGA and 41 AGA). Placentae and neonates were weighed at birth. Realtime quantitative PCR was performed to assess placental transcript abundance of GRB10 and PHLDA2 normalized to a panel of reference genes. Results: Placental GRB10 transcript abundance associated positively with placental weight (r = 0.307, P = 0.007), birth weight (r = 0.267, P = 0.019) and neonatal head circumference (r = 0.280, P = 0.014). Placental GRB10 transcript levels were significantly lower in male SGA placentae compared to the male AGA placentae. Placental PHLDA2 transcript abundance did not show any associations with maternal, placental or neonatal parameters. Discussion: Placental GRB10 expression was found to be associated positively with placental weight, birth weight, and neonatal head circumference, especially in males. Hence, we speculate that placental GRB10 plays a role in regulating fetoplacental growth and thereby in the pathophysiology of fetal growth restriction in the context of fetal gender. Highlights: Human placental GRB10 expression associates positively with placental weight and birth weight. Placental GRB10 expression is significantly lower in male SGA-compared to male AGA-placentae. Placental PHLDA2 expression is not associated with placental weight or birth weight.